The Relationship Between Knowledge and Attitudes of Nursing Students Towards Premarital Sex in Indonesia - Br Saragih, Dameria; Mailintina, Yurita; Panjaitan, Ribka Sabarina; Silaban, Merri; A. Salim, Indra Permata (MALATA SAINS INDONESIA, 2024)
Introduction: Nursing students, as prospective health workers, have a very important role in providing education and services to the community related to healthy sexual practices. The knowledge and attitudes of nursing students towards premarital sex in Indonesia are relevant subjects to be researched. Objectives: This study aims to fill the knowledge gap by investigating the knowledge and attitudes of nursing students towards premarital sex in Indonesia. Methods: This study used quantitative analytical methods with a cross sectional design. This research was conducted on 5 campuses organizing nursing education in Indonesia. Results: from 230 respondents, the mean value of sex was 1.07, the age of respondents was 1.94, knowledge was 1.94 and attitude was 1.85, then the Standard Error value of 0.022, 0.016, 0.010 and .0.29, the median value of 1.00, 2.00, 2.00 and 2.00, the value of Std Deviation 0.330, 0.240, 0.146 and 0.443, the variance value of 0.109, 0.057, 0.021 and 0.196 and the value of range 3, 1.1 and 2 of each variable. The majority have good knowledge (176.1) and sufficient attitudes (180.0). However, the number of respondents with less knowledge (5.0) and good attitude (41.1) is relatively less. The chi-square test showed a p-value of 0.000, showing a significant relationship between nursing students' knowledge and attitudes toward premarital sex. Conclusion: In this study, it was concluded that the knowledge and attitudes of nursing students have a close relationship. There is good knowledge so that students can control negative attitudes or actions towards premarital sex.